2019
DOI: 10.13057/tropdrylands/t030201
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition and aroma quality of five aromatic upland-rice accessions from Sumba Barat Daya District, East Nusa Tenggara Province, Indonesia

Abstract: Abstract. Arsa IGBA, Lalel HJD, Pollo R. 2019. Proximate composition and aroma quality of five aromatic upland-rice accessions from Sumba Barat Daya District, East Nusa Tenggara Province, Indonesia. Trop Drylands 3: 35-40. This research aimed to know the proximate composition and aroma quality of five aromatic upland-rice accessions from South West Sumba, East Nusa Tenggara Province and their correlation with the physical and chemical properties of the soil taken from the planting area of each accession. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The variety 3737 had a higher starch rate, and compared to those of B22 and Fofifa 123, the values were significantly different (p˂0,05). Adwita Arsa et al [32] have reported a comparable result with five upland rice varieties from Indonesia. Li et al [33] have found that the major component in rice flour is starch: 90% as a percentage of the dry matter, along with other varieties of rice.…”
Section: Nutritional Analysismentioning
confidence: 76%
See 1 more Smart Citation
“…The variety 3737 had a higher starch rate, and compared to those of B22 and Fofifa 123, the values were significantly different (p˂0,05). Adwita Arsa et al [32] have reported a comparable result with five upland rice varieties from Indonesia. Li et al [33] have found that the major component in rice flour is starch: 90% as a percentage of the dry matter, along with other varieties of rice.…”
Section: Nutritional Analysismentioning
confidence: 76%
“…This result is consistent with the values found by Ashongbon and Akintao [21] with rice starch from upland rice varieties from Nigeria (Igbemorice, EfonAlayerice): between 10.40 and 12.77%. The small variation in the moisture of rice starch could be attributed to the difference in cultivar [26,37], and also to the differences in the way the farmer handled the rice [32].…”
Section: Nutritional Analysismentioning
confidence: 99%